(untitled) (Journal of Pharma Insights and Research, 2025)
Cardiovascular diseases (CVDs) remain the leading cause of global mortality, with elevated low-density lipoprotein cholesterol (LDL-C) identified as a primary modifiable risk factor. While statins serve as the foundational therapy for lipid management, a significant proportion of patients fail to achieve recommended LDL-C targets due to intolerance or insufficient efficacy. The introduction of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors marked a significant advancement; however, the initial monoclonal antibody formulations require parenteral administration, limiting broad patient acceptance and accessibility. This review discusses about the emerging class of oral PCSK9 inhibitors, which aim to combine the potent efficacy of biologic agents with the convenience of oral dosing. The pharmacological mechanisms of novel small-molecule inhibitors and macrocyclic peptides, especially recent clinical data for candidates such as MK-0616 and AZD0780 are detailed in this review. Phase 2 clinical trials indicate that these oral agents can achieve LDL-C reductions comparable to injectable formulations, with safety profiles similar to placebo. Moreover, the challenges of oral bioavailability, the potential for synergistic therapy with statins, and the implications for global cardiovascular health were also discussed in this paper. The successful development of oral PCSK9 inhibitors represents a transformative step in preventative cardiology, potentially enhancing adherence and reducing the burden of atherosclerotic cardiovascular disease